2020
DOI: 10.3847/2041-8213/ab7931
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evolution of Type II Spicules Observed in Goode Solar Telescope On-disk Hα Images

Abstract: We analyze ground-based chromospheric data acquired at a high temporal cadence of 2 s in wings of the H α spectral line using Goode Solar Telescope (GST) operating at the Big Bear Solar Observatory. We inspected a 30 minute long H α -0.08 nm data set to find that rapid blue-shifted H α excursions (RBEs), which are a cool component of type II spicules, experience very rapid morphological changes on the time scales of the order of 1 second. Unlike typical reconnection jets, RBEs very frequently appear in situ wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Alongside QPPs, oscillatory reconnection can also be associated with quasi-periodic flows associated with spicules (e.g., De Pontieu & McIntosh 2010;De Pontieu et al 2011;Samanta et al 2019;Yurchyshyn et al 2020), as well as with observed periodicities in jets (Hong et al 2019) and in the formation, disappearance, and eruption of magnetic flux ropes (Shen et al 2018;Xue et al 2019). McLaughlin et al (2012b) were able to reproduce such observed periodicities through oscillatory reconnection in a 2D flux emergence model.…”
Section: Introductionmentioning
confidence: 71%
“…Alongside QPPs, oscillatory reconnection can also be associated with quasi-periodic flows associated with spicules (e.g., De Pontieu & McIntosh 2010;De Pontieu et al 2011;Samanta et al 2019;Yurchyshyn et al 2020), as well as with observed periodicities in jets (Hong et al 2019) and in the formation, disappearance, and eruption of magnetic flux ropes (Shen et al 2018;Xue et al 2019). McLaughlin et al (2012b) were able to reproduce such observed periodicities through oscillatory reconnection in a 2D flux emergence model.…”
Section: Introductionmentioning
confidence: 71%
“…Another important feature commonly observed in spicules is the rapid morphological transformations that they undergo both in space and time, including multiple splitting and branching (Yurchyshyn et al 2020). We refer to the examples shown in Fig.…”
Section: Spatial Distribution Of Spicules and Their Substructuresmentioning
confidence: 99%
“…Oscillatory reconnection is also a possible mechanism behind phenomena like periodicities observed in jets (Hong et al 2019), periodic behavior associated with the formation, disappearance, and eruption of magnetic flux ropes (Shen et al 2018;Xue et al 2019) and quasiperiodic flows associated with spicules in the solar atmosphere (e.g. De Pontieu & McIntosh 2010;De Pontieu et al 2011;Samanta et al 2019;Yurchyshyn et al 2020). For spicules, a 2D flux emergence model that triggered the oscillatory reconnection mechanism was able to reproduce such flows with the observed periodicities (McLaughlin et al 2012b).…”
Section: Introductionmentioning
confidence: 94%